Challenges and Successes in Raising a Child With Type 1 Diabetes and Autism Spectrum Disorder: Mixed Methods Study - Oser, Tamara K (J Med Internet Res, 2020)
BACKGROUND: Self-management of type 1 diabetes (T1D) requires numerous decisions and actions by people with T1D and their caregivers and poses many daily challenges. For those with T1D and a developmental disorder such as autism spectrum disorder (ASD), more complex challenges arise, though these remain largely unstudied. OBJECTIVE: This study aimed to better understand the barriers and facilitators of raising a child with T1D and ASD. Secondary analysis of web-based content (phase 1) and telephone interviews (phase 2) were conducted to further expand the existing knowledge on the challenges and successes faced by these families. METHODS: Phase 1 involved a qualitative analysis of publicly available online forums and blog posts by caregivers of children with both T1D and ASD. Themes from phase 1 were used to create an interview guide for further in-depth exploration via interviews. In phase 2, caregivers of children with both T1D and ASD were recruited from Penn State Health endocrinology clinics and through the web from social media posts to T1D-focused groups and sites. Interested respondents were directed to a secure web-based eligibility assessment. Information related to T1D and ASD diagnosis, contact information, and demographics were collected. On the basis of survey responses, participants were selected for a follow-up telephone interview and were asked to complete the adaptive behavior assessment system, third edition parent form to assess autism severity and upload a copy of their child’s most recent hemoglobin A(1c) (HbA(1c)) result. Interviews were transcribed, imported into NVivo qualitative data management software, and analyzed to determine common themes related to barriers and facilitators of raising a child with both ASD and T1D. RESULTS: For phase 1, 398 forum posts and blog posts between 2009 and 2016 were analyzed. Common themes related to a lack of understanding by the separate ASD and T1D caregiver communities, advice on coping techniques, rules and routines, and descriptions of the health care experience. For phase 2, 12 eligible respondents were interviewed. For interviewees, the average age of the child at diagnosis with T1D and ASD was 7.92 years and 5.55 years, respectively. Average self-reported and documented HbA(1c) levels for children with T1D and ASD were 8.6% (70 mmol/mol) and 8.7% (72 mmol/mol), respectively. Common themes from the interviews related to increased emotional burden, frustration surrounding the amount of information they are expected to learn, and challenges in the school setting. CONCLUSIONS: Caregivers of children with both T1D and ASD face unique challenges, distinct from those faced by caregivers of individuals who have either disorder alone. Understanding these challenges may help health care providers in caring for this unique population. Referral to the diabetes online community may be a potential resource to supplement the care received by the medical community.